Environmental changes and regime shift analysis in the southern Benguela using output from earth system models - Wilcox, Maxine (Department of Biological Sciences, 2025)
The accelerating pace of anthropogenic carbon emissions has triggered profound changes in Earth's climate, affecting marine ecosystems and fisheries globally. This study focuses on the southern Benguela, an integral region of the southern African Eastern Boundary Upwelling System (EBUS), investigating the potential impacts of climate change on this biologically productive region. Utilising data from the latest Coupled Model Intercomparison Project 6 (CMIP6), this research explores the implications of future extreme events, such as marine heatwaves, hypoxia, and acidification, on the southern Benguela ecosystem. Output from two earth system models (ESMs): the Geophysical Fluid Dynamics Laboratory (GFDL) and the Institut Pierre Simon Laplace (IPSL) was integrated with shared socioeconomic pathways (SSPs) to simulate environmental changes over time under historical scenarios (1970 – 2014), as well as low fossil fuel emission scenarios (SSP1-2.6) and high fossil fuel emission scenarios (SSP5-8.5). Trends in sea temperature, pH, chlorophyll-a concentration, integrated primary production, and oxygen concentration were plotted over the three different scenarios on the west and south coasts of the southern Benguela, over three depth levels. In addition, these time series were analysed using the sequential t-test algorithm for regime shift detection (STARS), in an attempt to detect any abrupt, long-term shifts. Projections under SSP1-2.6 tended to follow their historical trajectories, and displayed gradual changes over time. Under SSP5-8.5, however, future projections showed considerable temperature increases, conflicting trends in chlorophyll-a concentrations and integrated primary production, and concerning declines in pH and oxygen concentrations. Regime shifts were detected on both coasts for both ESMs, and tended to coincide temporally with extreme events observed in the environmental trends. In future scenarios on the west coast, clusters of regime shifts tended to be detected shortly after extreme events. Through a comparison of historical observations and hindcasts, the study also evaluated the reliability of the two ESMs, and it was found that GFDL generally exhibited better agreement with historical observations. The kind of ESM model-to-historic observation evaluations as carried out in this study play a crucial role in enhancing models' consistency and ought to be prioritised in the progression of CMIP7. Ultimately, this study contributes novel insights into the environmental dynamics of the southern Benguela. This research serves as a foundation for understanding future changes that may impact the region, providing valuable information for decision-makers, policymakers, and resource managers. In the face of climate change, these findings emphasise the need for adaptive and sustainable fisheries management strategies to ensure the conservation of the southern Benguela ecosystem and the millions of livelihoods it sustains.